Beginning Ubuntu Linux - Raggi, Emilio; Thomas, Keir.; Parsons, Trevor; Channelle, Andy.; Vugt, Sander van.; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
Ubuntu Linux is the fastest growing Linux-based operating system, and Beginning Ubuntu Linux, Fifth Edition teaches all of us$1 (Bincluding those who have never used Linux$1 (Bhow to use it productively, whether you come from Windows or the Mac or the world of open source. Beginning Ubuntu Linux, Fifth Edition shows you how to take advantage of Lucid Lynx. Based on the best-selling previous edition, Emilio Raggi maintains a fine balance between teaching Ubuntu and introducing new features. Whether you aim to use it in the home or in the office, you'll be introduced to the world of Ubuntu Linux, from simple word processing to using cloud services. You'll learn how to control the Ubuntu system, which you just installed from the book's DVD, as you are guided through common tasks such as configuring the system's graphical user interface (GUI), listening to audio CDs and MP3s, producing documents, using VoIP and chat, and of course, general system maintenance. This book also supplies a series of comprehensive tutorials on Ubuntu administration and security$1 (Bessential for any Ubuntu user$1 (Bwhile not neglecting matters pertaining to office applications and the cloud.s
Introducing the World of Linux -- Meet Ubuntu Linux -- GNU (3z(Bslash(3y (BLinux -- Installing Ubuntu -- Pre-installation Steps -- Installing Ubuntu -- Solving Installation Problems -- The No-Nonsense Getting Started Guide -- Booting Ubuntu for the First Time -- Getting Everything Up and Running -- How to Secure Your Computer -- Personalizing Ubuntu: Getting Everything Just Right -- Managing Your Data -- Working and Playing with Ubuntu -- A World of Applications -- Working with Text Files -- Making the Move to OpenOffice.org -- Communicating with Others -- Social Networks and Cloud Computing -- Digital Audio -- Movies and Multimedia -- Digital Photos -- Playing Games -- Keeping Your System Running -- Installing and Removing Software -- Understanding Linux Users and File Permissions -- Optimizing Your System -- Backing Up Data -- Scheduling Tasks -- Accessing Computers Remotely -- Taking Control of the System.s
Keywords: Computer science; User interfaces (Computer systems).; Computer Science; Computer Science, general; User Interfaces and Human Computer Interaction; Electronic books